Reflexões sobre uma intervenção para discutir gênero no ensino fundamental : possibilidades de práticas utilizando a literatura infantil - Botton, Andressa (2017)
This doctoral thesis presents an intervention performed at schools to debate gender issues with children and their teachers, understanding the importance that these debates start to happen in childhood. In a qualitative research, with a feminist gender approach, we performed three researches: documentary analysis of children's books, intervention with children and interviews with school professionals, in addition to notes in the field diary. Our goal was to develop and to assess possibilities for a psychoeducational intervention about gender with elementary school children, and to get to know the teachers’ perception about these issues in public school setting, approaching gender equality, women’s empowerment, and respect for sexual diversity as core themes. The intervention called “Talking about gender” took place in a range of ten meetings with twenty-two state public school first-graders, with six and seven years old, for the reading of children’s books and/or for carrying out interactive-reflective activities focused on the work with the themes mentioned above. Moreover, we performed semi-structured interviews with four pre-school teachers. We noticed that there have been some children’s books available in the market able to approach these three themes in a playful and responsible way, enhancing the work about gender with children. This is due to the fact that we were able to promote, in the researched classroom setting, debates about gender stereotypes, reflections about inequalities still thrusted on boys/men and on girls/women, and a collaborative construction of alternatives to fight gender inequalities in society. However, we acknowledge the lack of guidelines to educate and to inform teachers about working with gender at school, resulting in approaches based on personal experiences, often making them insecure about how to act. Therefore, we understand that the intervention we performed may be embraced by teachers and other professionals who intend to raise awareness about fighting the exclusion and the violence caused by gender inequality, to encourage the existence of (more) spaces for similar activities,and to spread the potential of such debates.